1997
DOI: 10.1093/oxfordjournals.eurheartj.a015358
|View full text |Cite
|
Sign up to set email alerts
|

Use of troponin-T concentration and kinase isoforms for quantitation of myocardial injury induced by radiofrequency catheter ablation

Abstract: Background Although there remains particular concern about late malignant ventricular arrhythmias arising from myocardial damage induced by catheter ablation, the extent of myocardial injury resulting from clinical ablation procedures has not been fully studied. We conducted a prospective, controlled study to investigate the use of two newer markers of myocardial integrity, troponin-T concentration and creatine kinase isoforms, and a traditional marker, creatine kinase-MB concentration, in the assessment of my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 20 publications
1
27
0
2
Order By: Relevance
“…Other studies on mixed cohorts of patients undergoing RF ablation have found a peak in markers of myocardial injury within the first few hours after ablation. 5,13 The findings of RF ablation time being an independent predictor of Troponin-T elevation, consistent with previous studies, 5,13 and higher extent of Troponin-T elevation in patients with persistent AF suggest that markers for myocardial injury relate to the extent of ablation, with more extensive ablation performed in patients with persistent forms of AF.…”
Section: Inflammation and Myocardial Injurysupporting
confidence: 88%
See 1 more Smart Citation
“…Other studies on mixed cohorts of patients undergoing RF ablation have found a peak in markers of myocardial injury within the first few hours after ablation. 5,13 The findings of RF ablation time being an independent predictor of Troponin-T elevation, consistent with previous studies, 5,13 and higher extent of Troponin-T elevation in patients with persistent AF suggest that markers for myocardial injury relate to the extent of ablation, with more extensive ablation performed in patients with persistent forms of AF.…”
Section: Inflammation and Myocardial Injurysupporting
confidence: 88%
“…3 Radiofrequency (RF) ablation for atrial arrhythmias is known to cause an increase in various markers of inflammation and myocardial injury. 4,5 Moreover, biomarker detection of myocardial injury is a key component in the third universal definition of myocardial infarction, and ablation is known to be a confounder. 6 A protracted elevation of CRP is seen after AF ablation and, after successful ablation of long-lasting persistent AF, a decline in CRP at 3 months is observed.…”
mentioning
confidence: 99%
“…157 Elevations after ablations are related to the amount of energy used but are usually modest. 161,162 This is also the case for ICD firings and endomyocardial biopsies. There also could be a variety of toxic insults that may exacerbate underlying ischemic heart disease or could function to damage the heart directly.…”
Section: Other Clinical Situations In Which Troponin Levels May Be Elmentioning
confidence: 94%
“…The cardiac isotype is specific for heart muscle injury. However, it has rarely been [3][4][5][6][7][8][9]. Cardiac troponin I (cTnI) has been shown to be more sensitive and specific than CK-MB and more specific than cardiac troponin T for the diagnosis of minor myocardial injury [10][11][12].…”
Section: Introductionmentioning
confidence: 99%